Collagenous Colitis and Spondylarthropathy. (3rd June 2012) - Ben Abdelghani, Kaouther; Sahli, Hana; Souabni, Leila; Chekili, Selma; Belhadj, Salwa; Kassab, Selma; Laatar, Ahmed; Zakraoui, Leith
Abstract : Collagenous colitis is a recent cause of chronic diarrhea. Cooccurrence with spondylarthropathy is rare. We describe two cases: one man and one woman of 33 and 20 years old were suffering from spondylarthropathy. They then developed collagenous colitis, 4 and 14 years after the onset of spondylarthropathy. The diagnosis was based on histological features. A sicca syndrome and vitiligo were observed with the female case. The presence of colitis leads to therapeutic problems. This association suggests a systemic kind of rheumatic disease of collagenous colitis.